2021
DOI: 10.48550/arxiv.2106.04602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Still Brighter than Pre-Explosion, SN 2012Z Did Not Disappear: Comparing Hubble Space Telescope Observations a Decade Apart

Curtis McCully,
Saurabh W. Jha,
Richard A. Scalzo
et al.

Abstract: Type Iax supernovae represent the largest class of peculiar white-dwarf supernovae. The type Iax SN 2012Z in NGC 1309 is the only white dwarf supernova with a detected progenitor system in pre-explosion observations. Deep Hubble Space Telescope images taken before SN 2012Z show a luminous, blue source that we have interpreted as a helium-star companion (donor) to the exploding white dwarf. We present here late-time HST observations taken ∼1400 days after the explosion to test this model. We find the SN light c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 72 publications
(143 reference statements)
1
8
0
Order By: Relevance
“…Kromer et al 2015;Yamanaka et al 2015;Magee et al 2016), at least a fraction of them occur inside a helium-rich CSM (Magee et al 2019;Jacobson-Galán et al 2019), while none has been observed in an elliptical galaxy host (Foley et al 2013). Lastly, at least one nearby SN Iax, SN 2012Z, has been securely associated with a luminous blue progenitor (McCully et al 2014;Stritzinger et al 2015;Yamanaka et al 2015;McCully et al 2021), with properties similar to those inferred for our ONe models prior to collapse (Section 3).…”
Section: Shell Burning and Envelope Ejection Prior To Collapse Near-supporting
confidence: 76%
“…Kromer et al 2015;Yamanaka et al 2015;Magee et al 2016), at least a fraction of them occur inside a helium-rich CSM (Magee et al 2019;Jacobson-Galán et al 2019), while none has been observed in an elliptical galaxy host (Foley et al 2013). Lastly, at least one nearby SN Iax, SN 2012Z, has been securely associated with a luminous blue progenitor (McCully et al 2014;Stritzinger et al 2015;Yamanaka et al 2015;McCully et al 2021), with properties similar to those inferred for our ONe models prior to collapse (Section 3).…”
Section: Shell Burning and Envelope Ejection Prior To Collapse Near-supporting
confidence: 76%
“…These winds can be the dominant source of luminosity at late times (≈ 1 year post explosion) lasting for at least a decade. Recent Hubble Space Telescope (HST) observations of SN 2012Z revealed an excess in its late-time luminosity that could be a result of remnant-driven winds (McCully et al 2021). Late time HST observations of SN 2021fcg will be valuable in probing the nature of its bound remnant.…”
Section: What Is the Progenitor Of Sn 2021fcg?mentioning
confidence: 99%
“…SN 2012Z-S1) has been interpreted as a He-star companion to the exploding WD (McCully et al 2014;Liu et al 2015). Interestingly, late-time observations taken about 1400 days after the explosion by the Hubble Space Telescope have shown that SN 2012Z is brighter than the normal SN 2011fe by a factor of two at this epoch (McCully et al 2021). This excess flux is suggested to be a composite of several sources: the shock-heated companion, a bound remnant that could drive a wind, and light from the SN ejecta due to radioactive decay (McCully et al 2021).…”
Section: Introductionmentioning
confidence: 99%